Mesenteric lymphadenopathy is a key to diagnosis of radiologically challenging pulmonary lymphoma - Lu, Pei‐Hsuan; Huang, Chung‐Yao; Jhou, Zong‐Yi; Huang, Wei‐Ming; Chen, Chia‐Hung; Huang, Chun‐Chao (Thoracic cancer, 2020)
Extranodal marginal zone B‐cell lymphoma (EMZBL), previously known as mucosa‐associated lymphoid tissue lymphoma, is the most common type of marginal zone B‐cell lymphomas. Primary pulmonary lymphomas only constitute 0.5% of primary lung cancer, but 90% of these are EMZBLs. Primary pulmonary lymphomas share similar imaging features with secondary pulmonary lymphomas. Imaging diagnosis is challenging because many benign and other malignant lung lesions can display similar features. Here, we demonstrate a 70‐year‐old male case with lung tumors and only mesenteric lymphadenopathy, which was eventually diagnosed as advanced pulmonary EMZBL with involvement of the mesenteric lymph nodes and bone marrow. Pulmonary masses have a wide differential diagnosis, but concurrent isolated mesenteric lymphadenopathy might be a radiological clue to pulmonary lymphoma. Key points Concurrent isolated mesenteric lymphadenopathy might be a radiological clue to pulmonary lymphoma. For nonspecific lung tumors, additional abdominal computed tomography (CT) scan might be helpful for diagnosis of possible lymphoma.